2016
DOI: 10.1007/s12195-016-0458-3
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Exosome Migration Across the Blood–Brain Barrier Model In Vitro

Abstract: The delivery of therapeutics to the central nervous system (CNS) remains a major challenge in part due to the presence of the blood-brain barrier (BBB). Recently, cell-derived vesicles, particularly exosomes, have emerged as an attractive vehicle for targeting drugs to the brain, but whether or how they cross the BBB remains unclear. Here, we investigated the interactions between exosomes and brain microvascular endothelial cells (BMECs) in vitro under conditions that mimic the healthy and inflamed BBB in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
340
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(372 citation statements)
references
References 76 publications
(112 reference statements)
6
340
1
Order By: Relevance
“…Compared to exosomes utilized in this investigation (130 nm), the Mϕ-derived extruded membrane vesicles had larger average diameter (218 nm), which may result in increased sequestration in peripheral organs causing lower brain transport. Besides, our study was consistent with the study showing that fluorescently labeled exosomes released from autologous dendritic cells was detectable in mouse brains 24 h after IV injection [55], and other recent study showing that HEK293T exosomes can penetrate the Transwell model of BBB transcellularly under inflamed conditions (TNF-α activated) [56]. …”
Section: Discussionsupporting
confidence: 92%
“…Compared to exosomes utilized in this investigation (130 nm), the Mϕ-derived extruded membrane vesicles had larger average diameter (218 nm), which may result in increased sequestration in peripheral organs causing lower brain transport. Besides, our study was consistent with the study showing that fluorescently labeled exosomes released from autologous dendritic cells was detectable in mouse brains 24 h after IV injection [55], and other recent study showing that HEK293T exosomes can penetrate the Transwell model of BBB transcellularly under inflamed conditions (TNF-α activated) [56]. …”
Section: Discussionsupporting
confidence: 92%
“…For example, several published reports have demonstrated that exosomes are capable of crossing the blood-brain barrier (BBB) when active neuroinflammation is present. [47][48][49] Neuroinflammatory cascades often result in the compromised integrity of the BBB, thereby allowing for large macromolecules and even cells to enter from the periphery. 50,51 In addition, some methods of manufacturing and labeling MEX use extended processing times, which may decrease their resulting functional properties.…”
Section: Mex Biodistributionmentioning
confidence: 99%
“…We identified uptake of our plasma derived EVs in the hCMEC/D3 cells line (Fig 2 and 3), supporting the findings of Chen et. al 2016 who identified internalization of exosomes derived from HEK 293T cells in endothelial cells (40). The same study show that the endothelial cells internalize the EVs by endocytosis via the trans-cellular route.…”
Section: Evs Cross the Bbb And Are Retained In Endothelial Cellsmentioning
confidence: 86%